HARMONIZING THE CUSTOMS LAWS OF THE EUROPEAN UNION AND THE RUSSIAN FEDERATION USED FOR PROTECTING INTELLECTUAL PROPERTY RIGHTS - Pavlovich Albov, Alexey; Kupriyanova, Ludmila; Gorbunov, Zakhar; Pavlovich Zhdanov, Sergey; Pavlovich Kamyshansky, Vladimir (Revista Inclusiones, 2019)
This article studies the legal framework of the Russian and EU customs laws. The analysis conducted demonstrates that the main directions of harmonizing the existing legislation and the protection of intellectual property rights in the coming years should be as follows: the alignment of regulatory standards in the field of customs regimes, the introduction of a new form of declaring intellectual property into the Russian legislation similar to the European legal tradition, electronic declaration and access to computer databases on customs clearance, the development of a unified package of certification documents for claiming intellectual property based on the WTO standards and the EU experience in codifying rules of customs clearance. The authors of the article have conducted a logical analysis and proved that experts in the sphere of intellectual property should work together to develop instructions ensuring the uniform understanding of expert competence, expert training and certification, as well as the mutual accreditation of expert structures.